Diagnosis and quantitative determination of phenolic compounds in plant residues of chickpea (Albayan Scientific Journal, 2023)
: Study was conducted at College of Science / University of Mosul, Department of Biology, It also included detection of some allelopathic compounds found in (shoot and root groups) residues chickpea plant Cicer arietinum L., and identification of phenolic compounds in chickpea plant residues using high-performance liquid chromatography (HPLC). The results of the preliminary detection of phenolic compounds present in the plant residues of shoot and root group weresaponins, tannins, terpenes, resins and flavonoids, As for alkaloids, their presence was proven in shoot, while not root system in. The results of analysis and identification of phenolic compounds in chickpea plant residues using high-performance liquid chromatography (HPLC) technique showed that the shoot contained(P-Hydroxy benzoic acid Quercetin, Chlorogenic acid, Benzoic acid,), while the root contained (Quercetin, Chlorogenic acid، Ferulic acid, Benzoic acid).
Keywords: phenolic compounds; chickpea; HPLC; root groups; shoot groups